A Novel 3D-Printed Device for Precise Percutaneous Placement of Cannulated Compression Screws in Human Femoral Neck Fractures. (11th June 2021) - Long, Cheng; Liu, Jin-hai; Chai, Xiang-ping; Liu, Xiang-feng; Duan, Zhi-xi
Abstract : Background . The aim of this study was to investigate the application of computer-aided design and 3D printing technology for percutaneous fixation of femoral neck fractures using cannulated compression screws. Methods . Using computed tomography data, an individualized proximal femur model was created with a 3D printer. The reduction of the femoral neck fracture and the placement of the cannulated compression screws were simulated on a computer. A 3D printing guide plate was designed to match the proximal femur. After demonstrating the feasibility of the 3D model before the surgical procedure, the guide needles and cannulated compression screws were inserted with the aid of the 3D-printed guide plate. Results . During the procedure, the 3D-printed guide plate for each patient matched the bone markers of the proximal femur. With the aid of the 3D-printed guide plate, three cannulated compression screws were accurately inserted into the femoral neck to treat femoral neck fractures. After screw placement, intraoperative X-ray examination showed results that were consistent with the preoperative design. The time taken to complete the procedure in the guide plate group was 35.3 ± 2.1   min, the intraoperative blood loss was 6.3 ± 2.8   mL, and X-ray fluoroscopy was only performed 9.1 ± 3.5 times. Postoperative radiographs showed adequate reduction of the femoral neck fractures. The entry point, entry direction, and length of the three cannulated compression screws were consistent with the preoperative design, and the screws did not penetrate the bone cortex. Conclusion . Using computer-aided design and 3D printing technology, personalized and accurate placement of cannulated compression screws can be realized for the treatment of femoral neck fractures. This technique can shorten the time required for the procedure and reduce damage to the femoral neck cortex, intraoperative bleeding, and the exposure of patients and healthcare staff to radiation.